2021
DOI: 10.21608/adjg.2021.76269.1388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Injectable Platelet Rich Fibrin (I-PRF) with Bone graft around Immediate Dental Implant in Esthetic Zone

Abstract: Purpose: Injectable Platelet Rich Fibrin (I-PRF) is an efficient method in periodontal wound healing and regenerating bone; thus, the purpose of the current research was to assess radiographic and clinical of I-PRF around the immediate dental implant in the esthetic zone with xenograft. Material and methods: Twelve patients with unrestorable tooth/teeth in the esthetic zone were selected. Patients were selected randomly and split into two groups; Group I (test group; n = 6) patients that received immediate imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Similarly, Reda et al, evaluated the benefit of adding i-PRF to xenograft around immediate implants. 6 months postoperatively, they recorded mean change in bone density in the group which received i-PRF and xenograft 154.16±42.44 versus 74.83±19.31 in the group which received only xenograft with a statistical significant difference in favor of the test group (35) . The increase in bone density in the present study and the previously mentioned ones may be justified by the conclusion stated by Wang et al, who observed that i-PRF has a noticeable effect on osteoblasts migration, differentiation, activation, proliferation and survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Reda et al, evaluated the benefit of adding i-PRF to xenograft around immediate implants. 6 months postoperatively, they recorded mean change in bone density in the group which received i-PRF and xenograft 154.16±42.44 versus 74.83±19.31 in the group which received only xenograft with a statistical significant difference in favor of the test group (35) . The increase in bone density in the present study and the previously mentioned ones may be justified by the conclusion stated by Wang et al, who observed that i-PRF has a noticeable effect on osteoblasts migration, differentiation, activation, proliferation and survival rate.…”
Section: Discussionmentioning
confidence: 99%